Technological innovation and network evolution - Lundgren, Anders, 1957- (London ; New York : Routledge, 1995)
Setting the stage. The act of insight. Novelty in thought and action: the emergence of digital image processing in Sweden. Critical revision of the emerging pattern.
Keywords: Technological innovations; Digital techniques; Sweden; Technological innovations -- Social aspects; Technological innovations -- Social aspects -- Sweden; Image processing -- Digital techniques